A Review on the Design of Hydrogels With Different Stiffness and Their Effects on Tissue Repair - Luo, Tianyi; Tan, Bowen; Zhu, Lengjing; Wang, Yating; Liao, Jinfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Tissue repair after trauma and infection has always been a difficult problem in regenerative medicine. Hydrogels have become one of the most important scaffolds for tissue engineering due to their biocompatibility, biodegradability and water solubility. Especially, the stiffness of hydrogels is a key factor, which influence the morphology of mesenchymal stem cells (MSCs) and their differentiation. The researches on this point are meaningful to the field of tissue engineering. Herein, this review focus on the design of hydrogels with different stiffness and their effects on the behavior of MSCs. In addition, the effect of hydrogel stiffness on the phenotype of macrophages is introduced, and then the relationship between the phenotype changes of macrophages on inflammatory response and tissue repair is discussed. Finally, the future application of hydrogels with a certain stiffness in regenerative medicine and tissue engineering has been prospected.